Trends of Aged Population in Nepal (Patan Prospective Journal, 2024)
Population ageing is the dynamic process of demographic & socio-economic transformation which reflects the increase in the share of the elderly on the total population, which is considered as natural phenomenon. There are 2.97 million older people in Nepal as of the 2021 census older population reached 10.21 percent population of Nepal. Average growth rate is 0.92 percent and the older population growth rate is 3.29 percent per year. Nepal’s total fertility is 1 percent below replacement level, infant mortality is around 23 per thousand live births and average life expectancy is now around 71 years. These indicators show ageing is increasing rapidly and the care giving burden may increase rapidly in the future due to the tendency of migration of the young population to foreign countries. In this context, the Nepal government needs to focus on how to manage the ageing population and provide quality services and social security for the growing older people of Nepal.